Study guide for introductory chemistry : a foundation introductory chemistry basic chemistry - Stovall, Iris (Lexington, Mass. : D. C. Heath, 1996)
Chemistry and Physics
Keywords: Chemistry; Measurement; Matter; Energy; Chemical reaction; Chemical composition; Gas; Matter; Acid; Electrochemistry; Radioactivity; Nuclear energy; Organic chemistry; Biochemistry